In silico development and validation of EST derived new SSR markers for drought tolerance in Cicer arietinum L. - Bhardwaj, Juhi; Kumari, Nilima; Ford, Rebecca; Yadav, Renu; Choi, Insoo; Kumar, Rajendra (The Indian Journal of Genetics and Plant Breeding, 2017)
Microsatellites have become a marker of choice in plant genetics and breeding research due to their unilocus, multiallelic and highly reproducible nature. In present study EST sequences isolated from chickpea root under water stress were assessed for the frequency, type and distribution of SSR motifs. Out of the 6400 ESTs (accession no. CDO 38847 to GR 394575), SSR sequences were identified in 348 singleton contigs and from these, 50 flanking primer pairs were designed. Out of these, 41 amplified a marker of the expected size range across nineteen diverse chickpea accessions. 11 of the primer pairs were size polymorphic with an average PIC value of 0.59 across the nineteen genotypes assessed.